Normirovanie trenirovocnych nagruzok s ispol'zovaniem pokazatelej energeticeskoj stoimosti upraznenija - Bulgakova, N. Z.; Volkov, N. I.; Popov, O. I.; Samborskij, A. G. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of this research was to study the parameters of the pulse sums and the power cost in exercises of the different capacity and limited duration. 26 athletes of the highest qualification (age 18-24 years, height 162-186 sm, weight 62-83 kg), specializing in swimming, running and speed skating, executed the series of exercises on cycle simulator with limited duration 10, 30, 60, 120 and 360 seconds. Exercises were carried out without limbering up. The deduced as the result of the research regression dependence can be used for the counting of the power expenses at known values of pulse cost of exercise. On its basis there is possible the severe quantitative estimation of the used training loads, their classification with the use of the found critical values of the parameters of the power expenses and the pulse sums of an exercise. The values resulted in the table of the pulse cost, fixed in the critical modes of loads, can be used by the development of the effective programs of the optimization of training in various kinds of sports.